The Interatheriinae (Mammalia, Notoungulata) of the Friasian sensu stricto and Mayoan (middle to late Miocene), and the fossils from Cerro Zeballos, Patagonia, Argentina. (3rd July 2019) - Vera, Bárbara; González Ruiz, Laureano; Novo, Nelson; Martin, Gabriel; Reato, Agustina; Tejedor, Marcelo F.
Abstract : The middle to late Miocene Friasian sensu stricto, Colloncuran and Mayoan South American Land Mammal Ages (SALMAs) were established based on the mammals recovered from the Río Frías, Collón Curá and Río Mayo formations, respectively (southern Argentina and Chile). Records of Interatheriinae (Notoungulata) from these sediments have been known since the first contributions of Ameghino and Roth, but most of this material has only been superficially revised or is almost unstudied. Based on these old collections and new interatheriine records from Cerro Zeballos (Chubut Province), we improve the diagnosis of Caenophilus tripartitus, describe new and peculiar characters for this taxon, consider Epipatriarchus bifidens as Protypotherium cf. colloncurensis, and propose Epipatriarchus as a junior synonym of Protypotherium . In turn, the holotype of Epipatriarchus innexus is here identified as the mesotheriid Trachytypotherium sp. Therefore, only two genera of Interatheriinae, Protypotherium and Caenophilus, are recognized in the Friasian sensu stricto and Mayoan. We identify Protypotherium cf. endiadys and a probable new species of Protypotherium for the Friasian sensu stricto, P . cf. colloncurensis and Caenophilus tripartitus for the Mayoan, and C. tripartitus, P. colloncurensis and P . cf. endiadys for Cerro Zeballos. An extended phylogenetic analysis is performed, including species from low latitudes and new data for P . colloncurensis and Caenophilus tripartitus, with the latter recovered as a sister taxon to Miocochilius federicoi . Both Protypotherium and Miocochilius are recovered as paraphyletic. The updated information we present provides a better knowledge of Interatheriinae for the middle to late Miocene of southern South America.